High-velocity stretching of polyolefin tapes. (January 2020) - Eichelter, Johanna; Wilhelm, Harald; Mautner, Andreas; Schafler, Erhard; Eder, Andreas; Bismarck, Alexander
Abstract: Stretched polyolefin films and tapes are used in many packaging applications, such as BigBags. Stretching is elongation of polymer tapes in one direction, resulting in improved mechanical properties. Both, amorphous and crystalline polymers are in principle stretchable but linear, unbranched macromolecules are highly stretchable. Hence, the stretchability of e.g. branched low density polyethylene (PE-LD) is lower than of high-density polyethylene (PE-HD). Basic requirements for stretching of thermoplastics are known, but correlations between material parameters and stretching behaviour are scarce. Moreover, stretching of polymers is usually studied with tensile tests at stretching velocities much lower (1–500 mm/min) than in industrial processes (400–1000 mm/s), while results from high-velocity stretching tests or on production machines have not been published as of yet. We investigated high-velocity (800 mm/s) stretching of PE-LD, PE-HD and isotactic polypropylene films and tapes and which stretching parameters resulted in maximum mechanical properties. It was found that sample geometry, temperature, and the degree of stretching have a significant influence on the properties of stretched tapes, e.g. higher stretching temperature resulted in higher mechanical properties and orientation of crystallites. Furthermore, about 80% of the maximum stretching degree resulted in maximum mechanical properties. Highlights: Custom made high velocity stretching unit in laboratory scale. High-velocity stretching experiments allowing for stretching velocities close to typical industrial production conditions. Differences between low and high-velocity stretching established. Correlations between the stretching behaviour and mechanical properties of unstretched and stretched tapes. Direct correlations found between raw material properties and stretching behaviour.